2018
DOI: 10.1177/1099800418811634
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Improves Mood Status and Quality of Life and Decreases Cortisol Levels in Fibromyalgia

Abstract: Background: Mood disturbances are implicated in the pathogenesis of fibromyalgia. The aim of this study was to assess the effect of different doses of melatonin on quality of life, mood status, pain, anxiety, and urinary cortisol levels in patients with fibromyalgia. Methods: After a 10-day baseline period for the collection of data about participants’ initial status, participants took different doses of melatonin for 10 consecutive days each, with placebo given during the 10 days either before or between mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…These findings are similar to previous research that studied women diagnosed with FM, which found that FM patients reported more severe symptoms of depression, anxiety, insomnia and fatigue than controls, which constitute typical bodily and mental symptoms accompanying FM pain [32]. Elevated levels of pain catastrophizing and negative affect have also been previously observed [33][34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to previous research that studied women diagnosed with FM, which found that FM patients reported more severe symptoms of depression, anxiety, insomnia and fatigue than controls, which constitute typical bodily and mental symptoms accompanying FM pain [32]. Elevated levels of pain catastrophizing and negative affect have also been previously observed [33][34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…According to Vis et al’s systematic review, the limited pharmacological treatment for reduced quality of life or fatigue in sarcoidosis patients are available ( 42 ). However, the use of melatonin can improve PCS in patients with fibromyalgia ( 43 ), delayed sleep phase syndrome ( 44 ), and chronic fatigue ( 45 ), While administration of melatonin cannot improve PCS in women with osteoporosis ( 46 ) and hemodialysis patients ( 47 ). In our study, administration of 3 mg melatonin for three months can improve subjective sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that melatonin is associated with modulation of mood, sexual maturation and body temperature. Also, it is beneficial in periodontology [45]. The interplay between melatonin and ROS is oxidized into N1-acetyl-N2-formyl-5methoxykynuramine (AFMK), which has high antioxidant activity [46].…”
Section: Melatonin; Physiology and Importancementioning
confidence: 99%